The effect of collagenase clostridium histolyticum on adhesion reduction in a rat knee arthrofibrosis model - (:unkn) unknown (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2021)
Objective: The aim of this study was to investigate whether collagenase clostridium histolyticum (CCH) reduces infra-articular fibrotic adhesion formation in a rat model of arthrofibrosis. Methods: A total of 24 male Wistar rats (7 months old, weighing 220 -275 g) were randomly and equally assigned to one of two groups: the collagenase group and the control group (n = 12 each). In each group, a partial capsulotomy. and sy novectomy were performed in knee. After a partial capsulotomy and synovectomy were performed in each group, the collagenase group received intra-articular CCH of 0.008 mg in 0.1 mL saline solution while the control group received the equal volume of intra-articular saline solution alone. After 6 weeks of surgery, the rats were sacrificed by decapitation, and the following outcome measures were collected. Knee range of motion (ROM) was measured using with a goniometer under 20 g force. Adhesion formation was rated using the macroscopic visual scoring system after the knee joint was exposed through a lateral parapatellar approach. Histological evaluation was performed on samples including connective tissue and fibrotic adhesions, and fibroblast cell numbers were measured performed per square. Levels of interleukin 1 (IL-1) and fibroblast growth factor (FGF) were assayed by ELISA from the intro-articular fluid. Results: The macroscopic visual scoring system was significantly lower in the collagenase group (median = 1, range = 0-2) than in the control group (median = 2, range = 1-3)(< 0.001). ROM was significantly higher in the collagenase group (102 degrees +/- 12.1 degrees) than in the control group (77 degrees-8.94 degrees) (P <0.001). The number of fibroblasts obtained from the scar tissue were considerably lower in the collagenase group (mean =16.5 +/- 2.74) compared to the control group (mean= 30.1 +/- 4.89) (P < 0.001). Levels of IL-1 and FGF were significantly lower in the collagenase group (mean = 18.6 ng/l +/- 4.39,mean = 36.3 ng/l +/- 2.03; respectively) compared to the control group (mean = 31.7ng/l +/- 3.75, mean = 38.7 ng/l +/- 2.19; respectively) (P < 0.001). Conclusion: Evidence from this study has revealed that CCH injection can inhibit the development of arthrofibrosis, decreasing the precursor inflammatory cytokines (IL-1 and FGF-1) and histologic fibrosis in a rat knee arthrofibrosis model.
Keywords: Collagenase; Arthrofibrosis; Rat; Interleukin; Fibroblast growth factor; IN-VITRO; MANAGEMENT; INJECTION; STIFFNESS; FIBROSIS; JOINT; GENE